2007
DOI: 10.1111/j.1365-2044.2007.04998.x
|View full text |Cite
|
Sign up to set email alerts
|

Systemic complications after head injury: a clinical review

Abstract: Summary Non‐neurological organ dysfunction is common after traumatic brain injury and is an independent contributor to morbidity and mortality. It represents a risk factor that is potentially amenable to treatment, and early recognition and prompt intervention may improve outcome. This article reviews the current evidence for the mechanisms and treatment of non‐neurological organ dysfunction after head injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
69
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 94 publications
(137 reference statements)
0
69
0
1
Order By: Relevance
“…Previous studies have indeed demonstrated that extracranial complications contribute to almost two-thirds of all deaths after severe TBI [3, 4]. As is known, the most frequently seen extracranial complications following TBI is infection [5]. The incidence of infection following TBI is obviously higher than other noncranial insults such as polytrauma, burn injury, and major surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indeed demonstrated that extracranial complications contribute to almost two-thirds of all deaths after severe TBI [3, 4]. As is known, the most frequently seen extracranial complications following TBI is infection [5]. The incidence of infection following TBI is obviously higher than other noncranial insults such as polytrauma, burn injury, and major surgery [6].…”
Section: Introductionmentioning
confidence: 99%
“…Although the clinical differences were not statistically significant, these data suggest alterations in the immune status which may not be directly related to the overall injury severity. Non-neurological organ dysfunctions via neuroendocrine pathways have been recognized to be a common complication after TBI (16). Moreover, TBI in itself has been demonstrated to induce inflammation, as expressed by the release of diverse pro-inflammatory cytokines (TNF-a, IL-1b, -6 and -8) along with metabolic alterations in the early post-traumatic state, both systemically and in remote organs such as the gut (17,18).…”
Section: Discussionmentioning
confidence: 99%
“…The intensive care management of head injury associated with nonneurological organ dysfunction and failure presents a significant challenge, because optimum treatment for the failing systemic organ system may have potentially adverse effects on the injured brain and vice versa. 10 Respiratory complications are most frequent, occurring in up to 80% of patients, with those with the severest injury being most at risk. Ventilator-acquired pneumonia is a particular problem and occurs in 45-60% of patients.…”
Section: General Aspects Of Carementioning
confidence: 99%
“…10 They represent risk factors that are potentially amenable to treatment, and early recognition and prompt intervention may improve outcome. The intensive care management of head injury associated with nonneurological organ dysfunction and failure presents a significant challenge, because optimum treatment for the failing systemic organ system may have potentially adverse effects on the injured brain and vice versa.…”
Section: General Aspects Of Carementioning
confidence: 99%